Optimization of different wet chemical routes and phase evolution studies of MnFe2O4 nanoparticles. Issue 10 (July 2019) - Baig, Mirza Mahmood; Yousuf, Muhammad Asif; Agboola, Philips Olaleye; Khan, Muhammad Azhar; Shakir, Imran; Warsi, Muhammad Farooq
Abstract: Facile and low cost micro-emulsion method for the synthesis of single phase manganese ferrite (MnFe2 O4 ) nanoparticles was explored. In an attempt to synthesize monodisperse and single phase manganese ferrite (MnFe2 O4 ) nanoparticles, micro-emulsion method using different oil phases such as dodecanol, toluene and low cost paraffin was adapted. Simple co-precipitation method was also followed for comparison purpose. In this facile approach, the strategy to control the particle size at nano-level has been explained in detail. Formation mechanism of single phase manganese ferrite and appearance of different phases (such as goethite, manganite, hematite, hausmanite, maghemite, magnetite, etc) by these synthesis methods have been investigated and discussed. The samples were annealed at various temperatures to probe the thermal stability. Effect of annealing under air and under vacuum was studied. Thermal gravimetric analysis (TGA) was used to study the phase transitions along with the investigation of appropriate annealing temperature for spinel ferrite formation. X-ray Diffraction (XRD) analysis was used to study the crystal structure and phase identification. Microstructural properties were studied using scanning electron microscopy (SEM). Fourier transform infrared spectroscopy (FTIR) was used to study the bond stretching (Metal-Oxygen) and cubic spinel structure of MnFe2 O4 .